Development and psychometric validation of the Dispositional Recovery and Dysfunction Inventory: a tool to assess for positive and negative cognitions following trauma exposure. Issue 2 (31st March 2022) - Moore, Brian A.; Hale, Willie J.; Judkins, Jason L.; Peterson, Alan L.
Abstract: Background: Recovery from trauma can be naturally occurring or facilitated through psychotherapy. Few brief measures exist to provide clinicians with dispositional, empirical assessments of patient's sentiments during psychotherapy. Aims: This manuscript presents the Dispositional Recovery and Dysfunction Inventory (DRDI), a measure created to assist clinicians in evaluating patient's treatment progress during psychotherapy, as well as evaluate its factor structure, reliability estimates, measurement invariance, and correlates. Method: The DRDI was created based on feedback from experts with experience treating posttraumatic stress disorder (PTSD) and was structurally validated in two distinct populations. Exploratory factor analysis was conducted in sample 1 consisting of ( n =401) university students. Confirmatory factor analysis, measure validity and structure validation were then conducted in sample 2 ( n =249) composed of 49% individuals with clinically significant PTSD symptoms. Results: Exploratory and confirmatory factor analysis revealed that the DRDI was best represented by a two-factor correlated traits model representing sentiments related to dispositional recovery and dysfunctional cognitions. The recovery subscale exhibited relationships with convergent measures including authenticity and psychological hardiness ( r values of .30 to .60). The dysfunctional beliefs subscale exhibited relationships with convergent measures: PTSD, depression, suicidality and stress ( r values of .55 to 80). Measurement invariance across gender and PTSD status was observed. Conclusion: Initial findings indicate that the DRDI has the potential to be a useful tool to assess individuals' beliefs about their propensity to recover from and thrive through adversity.